2018
DOI: 10.1093/femsle/fnx266
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ reduces biofilm quantity in Acidithiobacillus ferrooxidans through inhibiting Type IV pili formation

Abstract: Bioleaching is a promising process for 350 million tons of Jinchuan low-grade pentlandite. But high concentration of Mg2+ is harmful to bioleaching microorganisms. Interestingly, biofilm formation can improve leaching rate. Thus, it is actually necessary to investigate the effect of Mg2+ stress on Acidithiobacillus ferrooxidans biofilms formation. In this study, we found that 0.1 and 0.5 M Mg2+ stress significantly reduced the total biomass of biofilm in a dose-dependent manner. The observation results of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Oknin et al reported that Mg 2+ ions drastically downregulated the expression of two major operons in Bacillus species, which was tightly correlated to the synthesis of the extracellular matrix and thus mitigated biofilm formation . Tang et al suggested that Mg 2+ could suppress the growth of type IV pili, attenuating bacterial adhesion and subduing biofilm formation mediated by twitching motility . Additionally, the dissolution of Mg 2+ into the medium produces hydrogen and magnesium hydrate, exerting a pH buffering effect and shifting it toward the physiological pH .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oknin et al reported that Mg 2+ ions drastically downregulated the expression of two major operons in Bacillus species, which was tightly correlated to the synthesis of the extracellular matrix and thus mitigated biofilm formation . Tang et al suggested that Mg 2+ could suppress the growth of type IV pili, attenuating bacterial adhesion and subduing biofilm formation mediated by twitching motility . Additionally, the dissolution of Mg 2+ into the medium produces hydrogen and magnesium hydrate, exerting a pH buffering effect and shifting it toward the physiological pH .…”
Section: Resultsmentioning
confidence: 99%
“…75 Tang et al suggested that Mg 2+ could suppress the growth of type IV pili, attenuating bacterial adhesion and subduing biofilm formation mediated by twitching motility. 76 Additionally, the dissolution of Mg 2+ into the medium produces hydrogen and magnesium hydrate, exerting a pH buffering effect and shifting it toward the physiological pH. 77 This may help in disturbing cariogenic biofilm formation as well as inhibiting the decalcification of tooth hard tissue.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…At pH 0.7, the iron oxidation rate of the evolved L. ferriphilum still showed 320 mg L -1 h -1 at 20 gL -1 MgSO 4 . It was worthy to note that the higher concentration of MgSO 4 , the smaller the biomass produced by both the evolved strain and the starting strain, indicating that high concentration of MgSO 4 is detrimental to the production of biomass, previous studies also demonstrated that high concentration of Mg 2+ reduced the bio lm quantity (Tang et al, 2018).Therefore, the enhanced iron oxidation capacity may due to high ionic conductivity environment that improved electron transfer (Li et al, 2014).…”
Section: 4mentioning
confidence: 94%
“…But there was no significant effect between the biomass of Monascus M1 and the concentration of Mg 2+ . Tang et al (2018) showed that Mg 2+ stress significantly reduced the total biomass in a dose-dependent manner within a certain concentration range in Acidithiobacillus ferrooxidans. But in our present study, we did not find any correlation between the biomass and the concentration of Mg 2+ in Monascus M1 (Figure 1C).…”
Section: Effect Of Divalent Metal Ions On Biomassmentioning
confidence: 95%